(untitled) - Sutter, Ed (Berkeley, CA, 2002)
Show how to program embedded software systems, build a platform where an embedded system application can reside, and startup an embedded system project. The author covers exception handling, flash memory drivers, a flash file system, and serial and Ethernet connections. A familiarity with C is assumed. The CD-ROM contains the monitor package described in the book and Microcross GNU X-Tools.
Keywords: Embedded computer systems,Computer firmware,Hệ thống lệnh nhúng máy tính,Vi chương trình máy tính; Design and construction,Thiết kế và xây dựng